The prevalence of hazardous drinking in older New Zealanders - Towers A; Sheridan J; Newcombe D; Szabo A (Health Promotion Agency, 2018)
In a national survey of older adults, we compared the classification of hazardous versus non-hazardous drinkers based on the AUDIT-C and the Comorbidity Alcohol Risk Evaluation Tool (CARET). The CARET is an older adult-specific alcohol screen that assesses alcohol-related risks both based on consumption levels and the presence of factors increasing potential harm, including health conditions associated with alcohol use (such as diabetes), the use of alcohol-interacting medication (such as pain medications), symptoms of health issues or frailty (such as low mood, memory problems, and falls), and alcohol risk behaviours (such as drink-driving).